PERMOHONAN PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG OLEH KARYAWAN/BURUH AKIBAT TIDAK DIEKSEKUSINYA PUTUSAN PENGADILAN HUBUNGAN INDUSTRIAL (STUDI KASUS PUTUSAN NO. 20/PDT.SUS-PKPU/2019/PN NIAGA MDN) - Maura Meralda Harahap (LLPM Universitas Deli Sumatera, 2021)
PKPU Applications submitted by 11 PKPU Applicants who are Creditors of PT. Sumatra Beton Mandiri as PKPU Respondent based on the Medan Industrial Relations Court (PHI) Decision at the Medan District Court with Case Register No. 76/Pdt.Sus-PHI/2015 dated August 28, 2015. Whereas based on the Decision of the Industrial Relations Court, the Respondent PKPU has filed an cassation with the case of Reg. No. 450 K/ Rev. Sus-PHI/2015, which in its decision rejected the appeal from the Cassation Petitioner PT. Sumatra Concrete Independent. The type of research used in this research is normative juridical research. The nature of this research is descriptive analytical. The data used is secondary data which can consist of primary legal materials, secondary legal materials, and tertiary legal materials. The results of the discussion in this study are the Industrial Relations Court's decision can be used as the basis for a PKPU application referring to the conditions described above as stipulated in Article 2 paragraph 1 in conjunction with Article 8 paragraph 4 in conjunction with Article 222 paragraphs 1, 2 and 3 of the UUKPKPU as long as the PKPU application is submitted by 2 creditors, one of which is past due and can be billed. In the explanation of Article 2 paragraph 1 UUKPKPU that what is meant by debt that has matured and can be collected is the obligation to pay debts that have matured, either because it has been agreed upon, because of the acceleration of the collection time as agreed, due to the imposition of sanctions or fines by the competent agency. , or because of the decision of the court, arbitrator, or arbitral tribunal. The Judge's Decision on the PKPU Application with register No.20/Pdt.Sus-PKPU/2019/PN Niaga Mdn is in accordance with the principle of justice and based on applicable legal provisions so that both creditors and debtors are obliged to carry out the decision in good faith.